Neuroscience and Islamic Values in Learning Strategy Development - Ihsan; Ahmad Lahmi; Dasrizal Dahlan; Rosniati Hakim (Islamic Studies and Education Journal, 2025)
Advances in neuroscience have opened new horizons in education, particularly in understanding how the brain works in the learning process. This article examines the integration of neuroscientific findings with Islamic educational values ​​in designing effective, adaptive, and holistic learning strategies. Using a qualitative literature review approach, this article explores the concepts of brain function, the principles of neuroplasticity, and the role of emotions in learning, then links them to Islamic views on reason, spirit, and the formation of a perfect human being. The study results indicate that the learning process is strongly influenced by brain structure and function, including the involvement of emotions and meaningful experiences. Islamic education, through the concepts of reason and heart, aligns with a neuroscientific approach in developing a learning system based on compassion, personalization, and spirituality. Therefore, Islamic teachers and educational institutions need to understand the fundamentals of neuroscience to create adaptive and spiritually meaningful learning.